The Analysis of Subject-Verb Agreement Errors on Students’ Writing Descriptive Text - Nafisatul Hasanah; Mosleh Habibullah (Institut Agama Islam Negeri Madura, 2020)
Subject-verb agreement is a language system that is learned by students who study English, yet some students like the eighth graders of MTs Sunan Kalijaga still make errors in applying this rule in their writing. This study is aimed to find out the subject-verb agreement errors on students’ writing descriptive text in the eighth grade in MTs Sunan Kalijaga Larangan Luar Larangan Pamekasan and to know the factors which cause their errors. In this research, the researcher used a qualitative approach with content analysis and descriptive design. The data was obtained by observing the descriptive texts written by the eighth graders. Then, discussing and analyzing the subject-verb agreement within the writing. After knowing the errors, some students and the teacher were interviewed to know the factors which cause such errors. Documentations were also used to legitimize the data. From 25 texts which were collected by the researcher, there are 92 omission errors in subject-verb agreement, 22 addition errors, 44 misformation errors, and 3 misordering errors. Additionally, those kinds of errors are caused by two main factors, namely word for word translation and the lack of grammar. Those factors relate to interlingual and intralingual factors. In brief, there are still many errors of subject-verb agreement among the students’ writing of descriptive text in the eighth grade in MTs Sunan Kalijaga